(untitled) (Research, Society and Development, 2021)
Universities, as promoters of knowledge and social development, have led to the inclusion of the SDGs in their programs and internal agendas, through teaching, research and extension practices. In this sense, this research aims to analyze the scientific production on the Sustainable Development Goals (SDGs) developed in universities, in different countries, included in the Web of Science database, between 2016 and 2020. To this end, exploratory-descriptive research was carried out, using the VosViewer software, then an analysis was made of the bibliometric networks that characterize international production on the subject. With a qualitative focus, the content of the works with the greatest impact around this theme was studied, the results of which point to the formation of clusters of authors, organizations and countries. The most prominent terms revolve around the keywords defined as the focus of the study in the initial research. The publication with the highest citation score was: Sustainable Development Goals and sustainability teaching at universities: Falling behind or getting ahead of the pack?, by Leal Filho, W. (2019).